Concept of Monotheism in Isaiah 45 as a Basic Alternative to Addressing the Reality of Religious Plurality in Indonesia - Novita Sari Sembiring; Cindy Quartyamina Koan; Merry Kristina Rungkat (Khazanah Theologia, 2022)
Religious plurality is an unavoidable reality in Indonesia. This research seeks to explain the attitudes that Christians may embrace in responding to the reality of religious plurality in Indonesia. The alternatives to the study are based on the implications of Isaiah 45, which is part of the Christian Bible. Researchers looked at the characteristics of Isaiah 45 and the concept of monotheism to get the implications of the concept of monotheism in Isaiah 45 for alternatives to Indonesian Christians. This type of research is qualitative descriptive research with the use of hermeneutic methods and socio-historical approaches. Researchers conduct a literature study of sources related to the research topic. The results explain that the implications of the concept of monotheism in Isaiah 45 show that Yahweh, who is God, is not exclusive in relationships with mankind. Based on the implications of the concept of monotheism in Isaiah 45, Christians can choose transformative inclusive attitudes in establishing relations with other religious people.